Both baseline clinical factors and genetic polymorphisms influence the development of severe functional status in ankylosing spondylitis. - Ruxandra Schiotis (Public Library of Science (PLoS), 2012)
Functional severity in ankylosing spondylitis (AS) patients is variable and difficult to predict early. The aim of our study was to assess whether a combination of baseline clinical factors and genetic markers may predict the development of severe functional status in AS. We performed a cross-sectional association study on AS patients included in the Spanish National Registry of Spondyloarthropathies--REGISPONSER. Bath Ankylosing Spondylitis Functional Index (BASFI) was standardized by adjusting for disease duration since the first symptoms (BASFI/t). We considered as severe functional status the values of BASFI/t in the top of the 60th (p60), 65th (p65), 70th (p70), and 75th (p75) percentile. We selected 384 single nucleotide polymorphisms (SNPs) distributed in 190 genes to be analyzed. The study cohort included 456 patients with mean age 50.8(± 10.5) years and with mean disease duration since first symptoms 24.7 (± 10.1) years. Older age at disease onset and neck pain at baseline showed statistical significant association with severe BASFI/t. Polymorphisms associated in the allele frequencies test with severe BASFI/t in all classifications were: rs2542151 (p60 [P = .04], p65 [P = .04], p70 [P = .001] and p75 [P = .001]) and rs2254441 (p60 [P = .004], p65 [P = .02], p70 [P = .01] and p75 [P<.001]).. Genotype association, after adjustment for covariates, found an association in three of the four patients' classifications for rs2542151 and in two of the classifications for rs2254441.Forward logistic regression did not identify any model with a good predictive power for severe functional development.In our study we identified clinical factors and 24 polymorphisms associated with development of severe functional status in AS patients. Validation of these results in other cohorts is required.